Active queue management algorithm focusing on fairness and low delay - Cheng-long SU; Guang JIN; Xian-liang JIANG; Jun NIU (Tongxin xuebao)
The popularity of delay sensitive applications and high throughput applications in the Internet made the caches of routers and switches larger,resulting in the high latency and high jitter rate of network traffic.With the growth of mobile applications based on the high bandwidth non-response flows,the network bottleneck resource utilization becomes more unbalanced,and the resources distribution of the whole network was difficult to be guaranteed.In order to alleviate these problems,considering the delay control and suppression of high bandwidth non-response flow,an active queue management algorithm focusing on fairness and low delay named FLDA was proposed based on Sample-Match,L-LRU cache and probabilistic packets dropping.Experimental results show that under the interference with high bandwidth non-responsive flows,FLDA can better maintain the queue stability,the fairness of resource utilization of the bottleneck link and the low delay.